HBeAg levels at week 24 predict response to 8 years of tenofovir in HBeAg‐positive chronic hepatitis B patients. Issue 1 (11th October 2017) - Wong, D.; Littlejohn, M.; Yuen, L.; Jackson, K.; Mason, H.; Bayliss, J.; Rosenberg, G.; Gaggar, A.; Kitrinos, K.; Subramanian, M.; Marcellin, P.; Buti, M.; et al.
Summary: Background: Hepatitis B e antigen (HBeAg) seroconversion is a treatment endpoint for HBeAg‐positive CHB, and a necessary precursor to HBsAg loss. Biomarkers that predict serological outcomes would be useful. Aim: To evaluate the utility of measuring HBeAg levels for predicting HBeAg seroconversion and HBsAg loss under long‐term tenofovir (TDF) therapy. Methods: A total of 266 patients were enrolled into a phase III study of TDF vs adefovir (ADV) for 48 weeks in HBeAg‐positive patients, followed by open‐label TDF up to 384 weeks. Serum HBeAg levels were measured for subjects with samples available at both baseline and week 24 of treatment (n = 200). Analysis compared subjects who achieved HBeAg seroconversion by week 384 vs no HBeAg seroconversion. Results: HBeAg seroconversion rate was 52% by week 384. Time to HBeAg seroconversion was 80 weeks (IQR: 36‐162). HBeAg decline at week 24 was associated with HBeAg seroconversion (1.63 vs 0.90 log10 PEIU/mL, P = .002). The optimal threshold for identifying HBeAg seroconversion was HBeAg decline ≥2.2 log10 PEIU/mL at week 24, with HBeAg seroconversion achieved by 76% of patients, compared to 44% if HBeAg decline <2.2 log10 ( P < .0001). HBeAg decline ≥2.2 log10 PEIU/mL at week 24 was associated with HBsAg loss in genotype A or D patients (38% vs 15%, P = .03). Precore/basal core promotor variants were associated with lower baseline HBeAg levels, but not HBeAg seroconversion. Conclusion: Decline in HBeAg levels by week 24 was associated with HBeAg seroconversion and HBsAg loss in HBeAg‐positive chronic hepatitis B patients treated with long‐term TDF.